1989
DOI: 10.1007/bf00381423
|View full text |Cite
|
Sign up to set email alerts
|

Zopiclone in insomniac shiftworkers

Abstract: Fifty adult insomniac shiftworkers (47 males and 3 females) between the ages of 22 and 55 participated in this two-week, double-blind comparative study of the hypnotic properties and effects on mood and work performance of zopiclone 7.5 mg and placebo. All subjects took inactive medication on the first night of the study and then received either zopiclone or placebo for the following 13 nights according to randomization. Pre-study variables included a demographic profile, medical history, physical examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Eight pharmacological interventions met inclusion criteria (24,(61)(62)(63)(64)(65)(66)(67) (table 6). Mean study quality score was 18.1 (range: 11-24).…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight pharmacological interventions met inclusion criteria (24,(61)(62)(63)(64)(65)(66)(67) (table 6). Mean study quality score was 18.1 (range: 11-24).…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Zopiclone (7.5 mg) was administered in two different study groups which reported insomnia: workers at a security company and a car manufacturing plant. Zopiclone had positive effects on total sleep time (61, 67) and quality (67), as well as sleep efficacy (61) and induction (67). Three studies evaluated the use of Modafinil or…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Several studies have used benzodiazepine receptor agonist hypnotics. For example, treatment with temazepam (20 mg) single dose administered at bedtime, increased daytime sleep duration, but did not improve nighttime sleepiness [115], and zopiclone (7.5 mg), taken 30 minutes before bedtime, increased sleep quality in shift workers without negatively impacting night work performance [116]. …”
Section: Shift Work Disordermentioning
confidence: 99%
“…Figure 1 presents a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram showing reasons for study exclusions. In total, eight of the included trials were randomised controlled trials 12,[14][15][16][17][18][19][20][21] . The remainder were cross-over [22][23][24] and a parallel group design [25][26][27] .…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Five trials applied ICSD criteria for SWD in use at the time of the study; these were all studies of stimulants 12,14,15,20,26,27 . Interventions evaluated were hypnotic [21][22][23][24][25] and stimulant drugs 12,14,15,20,26,27 , cognitive behaviour therapy 17 , aromatherapy 18 , light therapy 19 and Shimian granules (a form of a Chinese herbal medicine) 16 . With one exception, the studies of hypnotics were carried out between 1989 and 2008, stimulants between 2005 and 2012 and the non-pharmacological interventions since 2013.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%